Time matters: Transcriptomic insights into temporally regulated reproductive and physiological processes in the life cycle of salps - Svenja J. Müller; Ilenia Urso; Sara Driscoll; Katharina Michael; Gabriele Sales; Cristiano de Pittà; Wiebke Wessels; Bettina Meyer (PLoS ONE, 2025)
Despite the increasing importance of salps and the recognition of their role as important players in food webs and biogeochemical cycles, their life cycle characteristics and physiology remain mysterious. This uncertainty encourages oversimplifying modeling approaches, leading to inaccuracies that may affect population dynamics results. This lack of knowledge is critical, making it difficult to adequately assess their sensitivity to global warming and their impact on ecosystems if their abundance and distribution change with rising seawater temperatures. Therefore, we generated a de novo transcriptome of Salpa fusiformis to further investigate the physiological processes involved in the life cycle of salps. We examined differentially expressed genes between both reproductive forms, blastozooids and oozoids, and detected a general form-specific difference among Salpa. Furthermore, we identified mainly temporally driven processes (energy delivery, cell communication, spermatogenesis) by studying gene expression profiles of different developmental stages of blastozooids of Salpa fusiformis. A life cycle that physiologically prepares blastozooids during the potential reproductive period, regardless of their fertilization status, may favor rapid response to favorable conditions and formation of salp blooms. Understanding the processes involved will contribute to a better assessment of their sensitivity to environmental change and support the implementation of their role in ecosystem models. In addition, the generated transcriptome was used to select and validate a set of potential reference genes for future qPCR applications. This will facilitate molecular studies of tunicates generally and stimulate future physiological studies on salps.